Beneficial Role of b-Amyrin from Toothbrush Tree Salvadora persica in Experimental Hyperoxaluria - Geetha, K.; Venkappayya, D.; Manavalan, R. (Asian Journal of Chemistry, 2010)
Naturally occurring pentacyclic triterpenes of plant origin have been identified as possessing a wide range of pharmacological effects. The triterpene b-amyrin was isolated from alcoholic extract (70 % v/v ethanol) of leaves of Salvadora persica and the effect of oral administration of b-amyrin on calcium oxalate urolithiasis has been studied in male Wistar albino rats. Ethylene glycol feeding resulted in hyperoxaluria as well as increased renal excretion of calcium, phosphate and oxalate. Increase in oxidative milieu in hyperoxaluria was also evident by increased lipid peroxidation (LPO) and decreased enzymic and non-enzymic antioxidants. Decrease in the activities of renal enzymes exemplified the damage induced by oxalate, which correlated positively with increased lipid peroxidation and increased oxalate synthesis. These abnormal biochemical aberrations were attenuated with b-amyrin. From the present study, it can be concluded that b-amyrin may serve as candidate for alleviating oxalate toxicity.